Assessment of the Mutagenicity of Propolis Compounds from the Brazilian Cerrado Biome in Somatic Cells of Drosophila melanogaster - Fábio Henrique Fernandes; Zaira da Rosa Guterres; Joaquim Corsino; Walmir Silva Garcez; Fernanda Rodrigues Garcez (Orbital: The Electronic Journal of Chemistry, 2019)
Few information on the biological properties of the chemical constituents of propolis produced by Apis mellifera from the Cerrado of Midwest Brazil has hitherto been reported. In the present work, the mutagenic properties of five compounds isolated from a sample of brown propolis from the aforesaid biome, namely, caffeic (1), p-coumaric (2), dihydro-p-coumaric (3), and acetylisocupressic (4) acids, and aromadendrin (5) have been assessed by performing the somatic mutation and recombination test (SMART) on wing cells of Drosophila melanogaster, using standard (ST) and high bioactivation (HB) crosses. This is the first report of assessment of the mutagenic potential of 2-4, and using the SMART assay for 5. No mutagenicity was induced by 1-3 and 5 in the descendants from the ST and HB crosses at all evaluated concentrations. However, 1 and 2, unlike 3, were shown to be toxic to descendants of both ST and HB crosses. A structure-activity relationship established among 1-3 revealed that a C-7/C-8 unsaturation is responsible for the toxic effect of 2 compared to 3, while an additional ortho-dihydroxy substitution at C-3 and C-4 confers to 1 the highest toxicity to D. melanogaster flies. Diterpene 4 proved mutagenic only after P450 activation, suggesting that it may act as a promutagen compound.DOI: http://dx.doi.org/10.17807/orbital.v11i5.1418